2021
DOI: 10.3390/cancers13184613
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Homeobox D9 Drives the Malignant Phenotype of HPV18-Positive Cervical Cancer Cells via Binding to the Viral Early Promoter

Abstract: Persistent infections with two types of human papillomaviruses (HPV), HPV16 and HPV18, are the most common cause of cervical cancer (CC). Two viral early genes, E6 and E7, are associated with tumor development, and expressions of E6 and E7 are primarily regulated by a single viral promoter: P97 in HPV16 and P105 in HPV18. We previously demonstrated that the homeobox D9 (HOXD9) transcription factor is responsible for the malignancy of HPV16-positive CC cell lines via binding to the P97 promoter. Here, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Various genetic alterations have been found unique to HPV-positive oral squamous cell carcinoma (OSCC), including distinctive mutational signatures, overall mutational burden, frequent copy number changes, and candidate driver events 59 . The abnormal expression of HOX genes has been positively correlated with HPV infection in HPV-associated cancer types such as cervical squamous cell carcinoma (CESC) and HNSCC 48 , 60 , 61 . With regards to the HPV-associated HNSCC, HOXB13, HOXC5, HOXC6, HOXC9, and HOXD11 were differentially expressed between HPV-positive and HPV-negative HNSCC ( p < 0.05, Supplementary Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Various genetic alterations have been found unique to HPV-positive oral squamous cell carcinoma (OSCC), including distinctive mutational signatures, overall mutational burden, frequent copy number changes, and candidate driver events 59 . The abnormal expression of HOX genes has been positively correlated with HPV infection in HPV-associated cancer types such as cervical squamous cell carcinoma (CESC) and HNSCC 48 , 60 , 61 . With regards to the HPV-associated HNSCC, HOXB13, HOXC5, HOXC6, HOXC9, and HOXD11 were differentially expressed between HPV-positive and HPV-negative HNSCC ( p < 0.05, Supplementary Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dysregulation of G1 cell cycle progression leads to tumor cell proliferation [33]. A previous study indicated that knockdown of HOXD9 increased the number of cells at the G1 phase by downregulating expression of the G1 checkpoint-related genes [14]. Furthermore, HOXD9 inhibition could enhance the expression of p53 [9], a key player in the cell cycle for repairing DNA damage [34].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, elevated levels of HOXD9 have been detected in various cancers, such as glioblastomas [8], cervical cancer [9], colorectal carcinoma [10], gastric cancer [11], hepatocellular carcinoma [12], and esophageal squamous cell carcinomas [13]. Deletion of HOXD9 could inhibit tumor cell proliferation and cause cell cycle G1 arrest, as well as weaken tumor-forming capacity [10][11][12]14]. Moreover, HOXD9 silencing induced apoptosis of tumor cells by activating the p53 pathway [9].…”
Section: Introductionmentioning
confidence: 99%
“…From 2000, different studies showed that HOXD9 regulates the early promoter of HPV16. Hayashi et al confirmed its role even in the regulation of HPV18, implementing the results in the research of a target therapy especially for the worse prognoses HPV-related histotypes [ 22 ].…”
mentioning
confidence: 99%